IDENTIFIKASI KEKERABATAN BAHASA NON-AUSTRONESIA DI WILAYAH PAKAI BAHASA KAO - Sunaidin Ode Mulae; Muhlis Fadel (Universitas Khairun, 2023)
This research aims to reconstruct non-Austronesian language relationships focus on the languages of the Kao ethnic, Pagu ethnic, Boeng ethnic, and Modole ethnicities in the Kao sub-district, West District, North District, Kao Teluk District and Malifut District. The method used in this research focuses on lexicostatistical methods to find similarities, differences, similarities in linguistic characteristics (shared of linguistics) in related vocabulary in the languages of the Kao ethnicity, Pagu ethnicity, Boeng ethnicity, and Modole ethnicity. The approach in this study uses a comparative historical and qualitative descriptive approach. The results found in this study are (1) the existence of kinship data for non-Austronesian languages in the Kao ethnic, Pagu ethnic, Boeng and Modole ethnic languages, (2) non-Austronesian languages in ethnic Kao, Pagu ethnic, Boeng ethnic have a close relationship compared to Modole ethnic (3) The basic vocabulary patterns of the Kao ethnic, Pagu ethnic, Boeng ethnic, and Modole ethnic form word structures Vowels (V), Vocal-Consonants (VC), Consonants-Vowels (CV), Consonants-Vocals-Consonants (CVC), Consonants-Vocals-Consonants-Consonants (CVCC), and Consonants-Consonants-Vocals (CCV). (4) The proto-kinship languages of the Kao, Pagu, Boeng, and Modole ethnicities have the proto-kinship languages of Kao, Pagu, and short Boeng (PKaoPB), which means that they come from one body, while the language of the Modole ethnic group has a language level of This microphylum that describes the Modole ethnic language has a kinship with the Kao ethnic language, whose tempo of separation is estimated to be 50-75 centuries ago. The conclusions of the study confirmed that the non-Austronesian language families, in this case the languages of the Kao ethnicity, Pagu ethnicity, Boeng ethnicity, and Modole ethnicity, have inter-ethnic kinship relationships that are built on one language family (language family).